2010
DOI: 10.1002/we.413
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steady deflections on the aeroelastic stability of a turbine blade

Abstract: This paper deals with effects of geometric non-linearities on the aeroelastic stability of a steady-state defl ected blade. Today, wind turbine blades are long and slender structures that can have a considerable steady-state defl ection which affects the dynamic behaviour of the blade. The fl apwise blade defl ection causes the edgewise blade motion to couple to torsional blade motion and thereby to the aerodynamics through the angle of attack. The analysis shows that in the worst case for this particular blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…As mentioned above, the interaction between blade motions and wind speed variations becomes more pronounced as wind turbines become larger. 3 Fluid-solid coupling dynamics also become more complex, and more serious coupling in wind turbines may cause blade damage more easily. For instance, during the operation of wind turbines, a minimum clearance must be maintained between the blade tips and the tower.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, the interaction between blade motions and wind speed variations becomes more pronounced as wind turbines become larger. 3 Fluid-solid coupling dynamics also become more complex, and more serious coupling in wind turbines may cause blade damage more easily. For instance, during the operation of wind turbines, a minimum clearance must be maintained between the blade tips and the tower.…”
mentioning
confidence: 99%
“…20 However, a fair number of the available commercial programs for wind turbine design still use simplified linear structural models, which cannot be applied to structures with considerable deformations. 3,[21][22][23] Furthermore, the blade behaviors are largely impacted by gravity, which induces excitation in the rotating blade and becomes a more crucial vibration source as dimensions of the wind turbine increases. 24 For this reason, it is necessary to understand the various nonlinear interactions including the effect of gravity, as well as the torsional DOF, on large-scale (larger than 5 MW) wind turbine blades.…”
mentioning
confidence: 99%
“… Torsion -(or "dynamic pitch") reduces damping of the first edgewise bending mode if torsion lags bending/edgewise deflection, with minimum damping at 90° phase lag (where torsion towards maximum angle of attack occurs simultaneously with maximum velocity in chordwise direction towards the trailing edge) [2]. Kallesøe [8] showed that bending of the blade under steady-state loading may result in such phased edge-torsion motion.…”
Section: Blade In Two-dimensional Quasi-steady Detached Flow (Strip mentioning
confidence: 99%
“…Figure 12 shows the variations of the aeroelastic damping in the edgewise modes with wind speed. The deflected blades led to a change in the distributions of the aerodynamic loads, which resulted in variations of the nonlinear structural coupling effect [35]. For these reasons, the damping of the edgewise modes are significantly affected by steady-state blade deflections.…”
Section: Dynamic Stability Analysis Under Normal Operating Conditionsmentioning
confidence: 99%